The mediating relationship between authentic leadership, organizational justice and engagement. (c2016) - Sidani, Zeina (2016)
In the face of today’s fast changing and competitive environment, each business aims to be distinguished, more innovative and agile. To do so, all members of the organization need to be engaged, from the janitor all the way to the top. However, encouraging employees to become engaged is not easy. This thesis examines the conditions which might lead to engaging employees. In particular, it focuses on two antecedents of engagement: authentic leadership and organizational justice. Two models are tested to better understand the mediating relationship between the three variables. Finally, after an extensive discussion of the statistical results, the practical implications of the study along with the future recommendations are suggested.